Modeling strategic investment decisions in spatial markets - Stefan Lorenczik; Raimund Malischek; Johannes Trüby (Institute of Energy Economics at the University of Cologne (EWI), 2014)
Markets for natural resources and commodities are often oligopolistic. In these markets, production capacities are key for strategic interaction between the oligopolists. We analyze how different market structures influence oligopolistic capacity investments and thereby affect supply, prices and rents in spatial natural resource markets using mathematical programing models. The models comprise an investment period and a supply period in which players compete in quantities. We compare three models, one perfect competition and two Cournot models, in which the product is either traded through long-term contracts or on spot markets in the supply period. Tractability and practicality of the approach are demonstrated in an application to the international metallurgical coal market. Results may vary substantially between the different models. The metallurgical coal market has recently made progress in moving away from long-term contracts and more towards spot market-based trade. Based on our results, we conclude that this regime switch is likely to raise consumer rents but lower producer rents. The total welfare differs only negligibly.
Keywords: L13; L72; C61; C70; 330; Investment; Coal; Oligopoly; Natural resources; Mathematical programming; Capacity Expansion; Spatial Markets; Equilibrium Problem with Equilibrium Constraints (EPEC)